An Analysis of Factors Affecting Loan Distribution A Case of Loans For Retirees at PT Bank Mandiri Taspen in the Period of 2017-2021 - Leticia, Geva; Vietha Devia SS (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Based on what is written in the Bank Mandiri Taspen 2020 Annual Report, Mandiri Taspen has strived to maintain sustainable growth and good performance even during the pandemic crisis. However, the improvement in the intermediation function of Mandiri Taspen's financial sector was not very strong, as evidenced by the credit contraction in January 2021. This research aims to determine the influence of Credit Interest Rates, Third Party Funds (DPK), and Return on Assets (ROA) on Credit Disbursement at PT. Bank Mandiri Taspen from 2017 to 2021. The data used in this study is quantitative data from secondary sources taken from Bank Mandiri Taspen's monthly financial reports. This research employs multiple linear regression analysis, classical assumption tests (Multicollinearity, Autocorrelation, Heteroskedasticity, and Normality), F-test, and T-test. Based on the regression results, the Credit Interest Rate does not have a negative and significant impact on credit disbursement, while the variables Third Party Funds (DPK) and Return on Assets (ROA) have a positive and significant impact on credit disbursement.